Complement Activation Is Associated With Crescents in IgA Nephropathy - Wang, Zi; Xie, Xinfang; Li, Jingyi; Zhang, Xue; He, Jiawei; Wang, Manliu; Lv, Jicheng; Zhang, Hong (Frontiers in Immunology, 2021)
Introduction: Crescents, especially those found at a percentage of greater than 50%, are often associated with rapid progression of kidney disease in IgA nephropathy(IgAN). The mechanism of crescents forming in IgAN is still unclear. In this study, we aimed to evaluate whether excess complement activation participates in the formation of crescents in IgAN. Methods: One hundred IgAN patients with various proportions of crescents—24 with 1-24%, 27 with 25-49%, 21 with 50-74% 12 with more than 75% and 16 without crescents—were included. Urinary concentrations of mannose-binding lectin(MBL), Bb, C4d, C3a, C5a and soluble C5b-9(sC5b-9) were measured at the time of biopsy. Receiver operating curves (ROCs) were performed to evaluate in predicting ability of renal survival for urine complement activation. In addition, historical C4d, C5b-9 and C3d were stained by immunohistochemistry. Results: IgAN patients with more than 50% crescent formation showed higher complement activation levels than the other patients (urinary C3a/Creatinine(C3a/Cr): 6.7295 ng/mg, interquartile range (IQR) 1.4652-62.1086 ng/mg vs. 0.1055 ng/mg, IQR 0-1.4089 ng/mg; urinary C5a/Cr: 15.6202 ng/mg, 4.3127-66.7347 ng/mg vs. 0.3280 ng/mg, IQR 0.0859-2.4439 ng/mg; urinary sC5b-9/Cr: 98.6357 ng/mg, 8.8058-1087.4578 ng/mg vs. 1.4262 ng/mg, 0.0916-11.0858 ng/mg, all P values <0.001). The levels of urinary MBL and C4d representing lectin complement pathway showed a linear association with the proportion of crescents (r=0.457 and 0.562, respectively, both P values <0.001). Combined urine complement products could increase the predict ability compared with crescents alone from 0.904 to 0.944(p=0.062) with borderline significance. Moreover, the glomerular C4d deposition rate elevated with the increase of proportions of crescents. Conclusion: Excess complement activation may be involved in the formation of crescents, especially diffuse crescent formation, in patients with IgAN. Urinary C4d correlated with the proportion of crescents and was a potential biomarker for disease monitoring in crescentic IgAN.